Kontribusi Sifat Biokimia Tanah sebagai Determinan Produktivitas Lahan Perkebunan Nanas (Ananas comosus [L.] Merr.) di Kabupaten Lampung Tengah - Kusuma handayani; Nisa Rachmania Mubarik; Atang Sutandi; Dwi Andreas Santosa; Untung Sudadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
One of the management challenges in pineapple cultivation at plantation scale is the still occurrence of disparity in land productivity across the cultivated area although the cropping practices have been implemented for many years. In the case of a pineapple plantation in Central Lampung Regency, contribution of soil biochemical properties in terms of various soil enzyme activities as a determinant factor of land productivity has never been elaborated. This research was aimed to study the relationships among biochemical and other soil properties with land productivity or pineapple yield at plantation scale. Rhizosphere soil-composite samples were taken purposively from 4 stations at the largest Indonesian pineapple plantation representing blocks with high and low yield and growth at vegetative and generative phase. Relationships amongst the studied parameters were evaluated using PCA and linear multiple regression analysis. The results showed significant contributions of the rhizosphere soil properties on the pineapple yield according to equation: Yield = 64.895 – 6.546 PCA1 +13.057 PCA2 – 7.722 PCA4 (R2= 0.612), where PCA1 consisted of soil available-P, available-K, and CEC; PCA2 was of soil base saturation, total microbe population, enzyme activities of cellulase and invertase, while PCA4 was of soil organic C, silt fraction, and phosphatase activities.